Optimal Control in Blood Flow Simulations - Guerra, Telma (2014)
Blood flow simulations can be improved by integrating known data into thenumerical simulations. Data assimilation techniques based on a variationalapproach play an important role in this issue. We propose a nonlinear optimalcontrol problem to reconstruct the blood flow profile from partial observationsof known data in idealized 2D stenosed vessels. The wall shear stress isincluded in the cost function, which is considered as an important indicatorfor medical purposes. To simplify we assume blood flow as an homogeneousfluid with non-Newtonian behavior. Using a Discretize then Optimize (DO)approach, we solve the nonlinear optimal control problem and we proposea weighted cost function that accurately recovers both the velocity and thewall shear stress profiles. The robustness of such cost function is tested withrespect to different velocity profiles and degrees of stenosis. The filteringeffect of the method is also confirmed. We conclude that this approach canbe successfully used in the 2D case